2019
DOI: 10.3389/fmicb.2019.02153
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-Derived Indole Metabolite Demonstrates Potent Multidrug Efflux Pump Inhibition in Staphylococcus aureus

Abstract: Efflux pumps are always at the forefront of bacterial multidrug resistance and account for the failure of antibiotics. The present study explored the potential of 2-(2-Aminophenyl) indole (RP2), an efflux pump inhibitor (EPI) isolated from the soil bacterium, to overcome the efflux-mediated resistance in Staphylococcus aureus. The RP2/antibiotic combination was tested against efflux pump over-expressed S. aureus strains. The compound was further examined for the ethidium bromide (EtBr) uptake and efflux inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…The post-antibiotic studies were performed according to Tambat et al (2019) with some modifications. S. aureus cells (∼10 5 CFU/ml) were treated with the two different concentrations, 4 μM (1 × MIC) and 8 μM (2 × MIC), of peptide-Ba49 in MHB medium.…”
Section: Methodsmentioning
confidence: 99%
“…The post-antibiotic studies were performed according to Tambat et al (2019) with some modifications. S. aureus cells (∼10 5 CFU/ml) were treated with the two different concentrations, 4 μM (1 × MIC) and 8 μM (2 × MIC), of peptide-Ba49 in MHB medium.…”
Section: Methodsmentioning
confidence: 99%
“…These data indicate that the addition of DPM does not seem to exert a significant effect on the PAE of erythromycin and clarithromycin. Tambat et al [ 44 ] indicated that an indole of microbial origin, the 2-(2-aminophenyl) indole, could increase the PAE of ciprofloxacin against gram-positive bacterium S. aureus expressing efflux pump NorA by 1.1–1.9 h. For example, the combination of ciprofloxacin (8 μg/mL) and EPI 2-(2-aminophenyl) indoles (32 μg/mL) could extend the PAE for the S. aureus from 1.43 h (8 μg/mL ciprofloxacin alone) to 3.33 h. So far, few studies have reported that EPIs could extend the PAE of antibiotics against gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The H33342 and EtBr dye accumulation assays were performed according to the method described in a previous report [ 44 ], with some modifications. The E. coli Kam3/pSYC- acrB solution for the dye efflux assay was prepared as described in Section 3.5 .…”
Section: Methodsmentioning
confidence: 99%
“…The synergy of tridecaptin M with other antibiotics was initially identified by checkerboard assay [ 21 , 53 ]. Briefly, in a 96-well plate, the concentration of tridecaptin M was varied vertically, whereas the antibiotics were varied horizontally in a matrix of 8 × 12.…”
Section: Methodsmentioning
confidence: 99%
“…The inoculum was prepared in a similar way as for MIC determination, and the plates were kept at 37 °C for MIC observation in combination. The fractional inhibitory concentration index (FICI) was calculated for each antibiotic to identify the synergistic effect of tridecaptin M [ 53 ] using following equation: …”
Section: Methodsmentioning
confidence: 99%